Review of Cathepsin K Inhibitor Development and the Potential Role of Phytochemicals - Dong Oh Moon (Molecules)
Cathepsin K plays a pivotal role in bone resorption and has emerged as a prominent therapeutic target for treating bone-related diseases such as osteoporosis. Despite significant advances in synthetic inhibitor development, none have achieved FDA approval due to safety and efficacy challenges. This review highlights the potential of phytochemicals as alternative inhibitors, emphasizing their natural origin, structural diversity, and minimal adverse effects. Key phytochemicals, including AC-5-1, Cycloaltilisin 6, Cycloaltilisin 7, Nicolaioidesin C, and Panduratin A, were examined for their inhibitory activities against cathepsin K. While these compounds exhibit varying IC50 values, their docking studies revealed significant interactions within Cathepsin K’s active site, particularly involving critical residues such as Cys25 and His162. However, challenges such as lower potency compared to synthetic inhibitors and limited in vivo studies underscore the need for structural optimization and comprehensive preclinical evaluations. This review discusses biological insights, current limitations, and future strategies for advancing phytochemical-based inhibitors toward clinical applications in managing Cathepsin K-associated diseases.